SA Rugby Injury and Illness Surveillance and Prevention Project (SARIISPP), Super Rugby Unlocked and the Carling Currie Cup Premiership Competition, Injury Surveillance Report 2020/21 - Starling, L.; Readhead, C.; Viljoen, W.; Paul, L.; Lambert, M. (South African Journal of Sports Medicine, 2021)
As part of the SA Rugby Injury and Illness Surveillance and Prevention Project (SARIISPP), the Carling Currie Cup 2020/21 Premiership Division Competition (the `Carling Currie Cup`) injury data were recorded throughout the tournament by the medical doctors and medical support staff of the respective teams. All seven teams were required to record every match and training injury that occurred in their team.The injury rate of Time-Loss injuries for the Carling Currie Cup 2020/21 was 91 (76 to 106) injuries per 1000 player hours (mean and 95% confidence intervals), which is higher than the international rate of 81 (63 to 105) injuries per 1000 player hours [1], but within the expected limits of season-to-season variation for the Carling Currie Cup. This equates to 1.8 injuries per team per match.